(untitled) (Analysis in Theory and Applications, 2013)
In this paper, we shall deal with the boundedness of the Littlewood-Paley operators with rough kernel. We prove the boundedness of the Lusin-area integral μ_Ω,s and Littlewood-Paley functions μ_Ω and μ^*_λ on the weighted amalgam spaces (L^q_ω,L^p)^α(R^n) as 1 < q≤ α < p≤ ∞.